2021
DOI: 10.1002/cey2.113
|View full text |Cite
|
Sign up to set email alerts
|

Carbon material‐based anodes in the microbial fuel cells

Abstract: For the performance improvement of microbial fuel cells (MFCs), the anode becomes a breakthrough point due to its influence on bacterial attachment and extracellular electron transfer (EET). On other level, carbon materials possess the following features: low cost, rich natural abundance, good thermal and chemical stability, as well as tunable surface properties and spatial structure.This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(52 citation statements)
references
References 141 publications
0
52
0
Order By: Relevance
“…This excellent performance of graphene aerogels has been attributed to the lower density and high SAs of graphene aerogels. Similarly, in another study, graphene‐based aerogels have shown the power volume of 750 W/m 3 299,300 . Similarly in another study, poly (diallylydimethylammoniumchloride)‐functionalized graphene (PDDA‐rGO) have shown excellent peak power at 5.029 W/m 2 .…”
Section: Methodsmentioning
confidence: 70%
See 2 more Smart Citations
“…This excellent performance of graphene aerogels has been attributed to the lower density and high SAs of graphene aerogels. Similarly, in another study, graphene‐based aerogels have shown the power volume of 750 W/m 3 299,300 . Similarly in another study, poly (diallylydimethylammoniumchloride)‐functionalized graphene (PDDA‐rGO) have shown excellent peak power at 5.029 W/m 2 .…”
Section: Methodsmentioning
confidence: 70%
“…Similarly, in another study, graphene-based aerogels have shown the power volume of 750 W/m 3 . 299,300 Similarly in another study, poly (diallylydimethylammoniumchloride)-functionalized graphene (PDDA-rGO) have shown excellent peak power at 5.029 W/m 2 . PDDA enhances the power density by its excellent electron withdrawing effect, which not only makes kinetic faster but also helps in transferring electrons at faster rate.…”
Section: Methodsmentioning
confidence: 83%
See 1 more Smart Citation
“…Graphene, as one of the potential 2D materials, offers an ideal platform for next-generation disruptive technology [ 91 , 92 ]. In recent years, with the development of new ink formulations related to effective printing technologies (including screen printing, gravure printing, spray coating, inkjet printing, and extrusion-based printing), interest in the use of graphene and its derivatives to make functional inks has grown exponentially [ 90 ].…”
Section: Categories Of Go-based Materials Involving Dyes and Pigmentsmentioning
confidence: 99%
“…[1,10] Among them, due to their good electrical conductivity, low price and chemical stability, carbon-based materials have received significant interest and been widely applied as the anode materials. [1,[17][18] Recently, to accomplish an enhanced performance and lifetime, modifications have been conducted on the conventional carbon materials, including nanostructure design, heteroatom doping, functionalized surface and composites with metals and polymers. [10] In this Review, the structure-performance relationship of MFCs based on carbon materials is demonstrated; advanced modification strategies for a synergy between solid electrode surface and electroactive bacteria and an improved bioelectricity generation are introduced; potential solutions for future MFC designs are also proposed.…”
Section: Introductionmentioning
confidence: 99%